Novel computational and drug design strategies for inhibition of monkeypox virus and Babesia microti: molecular docking, molecular dynamic simulation and drug design approach by natural compounds - Akash, Shopnil; Mir, Showkat Ahmad; Mahmood, Sajjat; Hossain, Saddam; Islam, Md. Rezaul; Mukerjee, Nobendu; Nayak, Binata; Nafidi, Hiba-Allah; Bin Jardan, Yousef A.; Mekonnen, Amare; Bourhia, Mohammed (Frontiers in Microbiology, 2023)
The alarming increase of tick-borne pathogens such as human Babesia. microti is an existential threat to global public health. It is a protozoan parasitic infection transmitted by numerous species of the genus Babesia. Secondly, Monkeypox has been an emerging public health crisis recently, and the virus has spread to the whole world during the post-COVID-19 period with a very rapid transmission rate. These two novel pathogens are making a new concern to human health globally and have become a significant obstacle for contemporary medicine development and the economy of the whole world. Currently, no approved medication for treating this disease. So, this research gap encourages us to find a potential inhibitor from a natural source.In this study, a series of natural plant-based biomolecules have been subjected to indepth computational investigation to find the most potent inhibitors targeting major pathogenic proteins responsible for the diseases caused by these two pathogens.Result: Among them, most of the selected natural compounds are predicted to bind firmly with the targeted proteins, which are crucial in the replication of these novel pathogens. Besides, all the molecules have outstanding ADMET properties like highly aqueous solubility, greater human gastrointestinal absorption rate, and free from any carcinogenic or hepatotoxic effects; most of them followed Lipinski's rule. Finally, the stability of the compounds was determined by molecular dynamic simulation (MDs) for 100 ns. During MDs, we observe that the mentioned compounds have exceptional stability against selected pathogens.These advanced computational strategies reported that eleven lead compounds, including Dieckol and Amentoflavone, exhibited high potency, excellent drug-like properties, and no toxicity. These compounds demonstrated strong binding affinities against the target enzymes, especially Dieckol, which displayed superior stability during molecular dynamics simulations. The MM/PBSA method confirmed the favorable binding energies of Amentoflavone and Dieckol. However, further in vitro and in vivo studies are necessary to validate their efficacy. Our research highlights the role of Dieckol and Amentoflavone as promising candidates for inhibiting both Monkeypox and Babesia microti, showcasing their multifaceted role in combating these pathogens.